Morphological and functional state of the epithelial cells in submandibular salivary glands after repeated amputations of the incisor teeth in adult rats - V. V. Ivanova; I. V. Milto; I. V. Sukhodolo (Бюллетень сибирской медицины, 2018)
Purpose. To evaluate a morphofunctional state of the epithelial cells of the acini and ducts of submandibular glands of mature rats after repeated incisors amputation.Materials and methods. The experiment was performed on mature (2 months) white male rats, divided into groups: intact, control group and a group of rats subjected to repeated incisors amputation. Applying histological, histochemical and morphometric methods, we evaluated the morphological and functional state of the epithelial cells in submandibular glands of adult rats at 2, 3, 4, 6, 8, 10 and 12 weeks after repeated amputation of the incisor teeth.Results. There is an increase of submandibular gland acini area at the 3–10 week after repeated incisors amputation. The functional activity of the submandibular glands ducts and acini cells decreases at the 2–4 week of the experiment.Conclusion. As a result of repeated incisors amputation in rat submandibular glands acini and ducts epithelial cells develop reversible structural and functional changes, which are leveled by the 12th and 6th week of the experiment, respectively.